2021
DOI: 10.3390/molecules26061781
|View full text |Cite
|
Sign up to set email alerts
|

Novel Processes for the Extraction of Phenolic Compounds from Olive Pomace and Their Protection by Encapsulation

Abstract: Olive pomace, the solid by-product derived from olive oil production consists of a high concentration of bioactive compounds with antioxidant activity, such as phenolic compounds, and their recovery by applying innovative techniques is a great opportunity and challenge for the olive oil industry. This study aimed to point out a new approach for the integrated valorization of olive pomace by extracting the phenolic compounds and protecting them by encapsulation or incorporation in nanoemulsions. Innovative assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 77 publications
2
36
1
2
Order By: Relevance
“…Similar to our results, major compounds of olive pomace were reported by Skaltsounis [40][41][42]. Among the major phenolic compounds of OPE, hydroxytyrosol has gained attention due to having health properties such as antioxidant activity, and anti-inflammatory and antimicrobial properties [5,6]. In this study, prepared nanoparticles showed mean particle size in the range of 304.1-318 nm for blank and OPE-loaded RSGNPs and 425.2-490 nm for blank and OPE-loaded CSGNPs, respectively (Table 3).…”
Section: Physicochemical Analysis Of Opp Rsg and Csgsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to our results, major compounds of olive pomace were reported by Skaltsounis [40][41][42]. Among the major phenolic compounds of OPE, hydroxytyrosol has gained attention due to having health properties such as antioxidant activity, and anti-inflammatory and antimicrobial properties [5,6]. In this study, prepared nanoparticles showed mean particle size in the range of 304.1-318 nm for blank and OPE-loaded RSGNPs and 425.2-490 nm for blank and OPE-loaded CSGNPs, respectively (Table 3).…”
Section: Physicochemical Analysis Of Opp Rsg and Csgsupporting
confidence: 89%
“…Olive pomace contains many phenolic compounds with potential influence on human health, such as hydroxytyrosol, tyrosol, and luteolin [4]. The primary phenolic compounds of olive pomace are oleuropein (1.22-13.50 mg/g), hydroxytyrosol (0.61-8.70 mg/g), tyrosol (0.13-1.115 mg/g), luteolin (0.02-0.14 mg/g), vanillin (0.92-3.64 mg/g), and rutin (0.21-1.70 mg/g) [5,6]. However, phenolic compounds have poor stability, low solubility, low bioavailability and are easily decomposed when exposed to both environmental (light, oxygen, temperature, humidity) and gastrointestinal (pH, digestive enzymes) system conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of olive leaf extracts (Da Rosa et al., 2019; Zam, 2019) or pure compounds like hydroxytyrosol (HT) (Bermúdez‐Oria et al., 2018; Fortunati et al., 2017) in biodegradable films and coatings as antioxidant agents have been proposed as a sustainable alternative to chemical additives. However, the effectiveness of phenolic compounds may be comprised by their low water solubility and stability, rapid oxidation, and high susceptibility to environmental factors (e.g., temperature, humidity, pH, and light), which may deteriorate the functional properties of films and coatings and lead to the loss of their bioactivity (Chanioti et al., 2021). To resolve these issues, encapsulation techniques, including spray drying, freeze drying, and emulsification, were applied to entrap phenolic‐rich extracts from olive byproducts, improve their antioxidant capacity and stability during storage, and allow their controlled release.…”
Section: Olive Byproducts As Source Of Active Agentsmentioning
confidence: 99%
“…To resolve these issues, encapsulation techniques, including spray drying, freeze drying, and emulsification, were applied to entrap phenolic-rich extracts from olive byproducts, improve their antioxidant capacity and stability during storage, and allow their controlled release. Due to the commercial availability of olive leaf extracts, more studies on the encapsulation of olive leaf extracts were performed when compared to those dealing with encapsulation of extracts from other olive byproducts F I G U R E 2 Diversified applications of olive byproducts from the olive oil industry (Chanioti et al, 2021;Paulo & Santos, 2020). Different wall materials, including chitosan, maltodextrin, and polylactic acid, were used for the encapsulation of phenolics obtained from olive byproducts (Chanioti et al, 2021).…”
Section: Olive Leavesmentioning
confidence: 99%
“…That is why NaDES have been previously employed for the extraction of phenolic compounds from natural sources [17,19,21]. In addition, these solvents have enabled the extraction of phenolic compounds in combination with advanced extraction techniques such as ultrasound-assisted extraction (UAE), homogenate (HAE), high hydrostatic pressure (HHPAE), pressurized liquid extraction (PLE), and microwave-assisted extraction (MAE) [22][23][24][25]. The main advantages that these extraction techniques present over conventional ones are the reduction of operation time and adverse ecological effects, the decrease in the amount of solvent employed, economizing the operation cost, and maintaining the quality of the compounds of interest.…”
Section: Introductionmentioning
confidence: 99%